Borg’s category ratio-scale (CR-10) is useful to predict the onset of blood lactate accumulation (OBLA) in young Mexicans adults, regardless their body mass - Ramos-Jiménez, Arnulfo; Wall-Medrano, Abraham; Hernández-Lepe, Marco A.; Chávez-Treviño, Gregorio; Guereca-Arvizuo, Jaime; Hernández-Torres, Rosa Patricia (CIENCIA ergo-sum; Vol. 26 Núm. 1 (2019): CIENCIA ergo-sum (marzo-junio 2019)DO - 10.30878/ces.v26n1a7, 2018)
Aim: To evaluate the predictive value of Borg’s category ratio-scale (CR-10; 1-10) toward the onset of blood lactate accumulation (OBLA). Methods: 91 young Mexicans performed three non-consecutive sub-maximal exercise tests. Heart rate (HR), blood lactate and oxygen uptake were recorded at each CR-10 rating. Regression equations, reliable HR and CR-10 cut-off points of OBLA were then calculated. Results: HR (86 beats/min) and CR-10 (4.5) predicted OBLA with the same certainty, regardless the subject’s body mass. CR-10, HR and oxygen uptake, independently explained more than 60% of the associated variance to OBLA. Conclusions: CR-10 is useful to predict OBLA with almost the same certainty that HR, regardless the subject’s body mass.